Exploratory Analysis of Students’ Score - Jude, Iroka; Mamidu, Moses Joanna (Mikailalsys Journal of Mathematics and Statistics, 2025)
The main thrust of this study was to determine the effect of Sex, Age, School, and Mode of Entry on performance of students in the subject Biology using Univariate Analysis of variance for the four factors (Sex, Age, School, and Mode of Entry) at two levels each factorial design. The case study is a single random sampling of 100 students selected from the 150 in a class of 200 level students from the Department of Biochemistry, Biological Sciences and Microbiology, Federal University Wukari, Taraba State, Nigeria. To achieve the purpose of this study, hypotheses were formulated to direct the study. Literature review was carried out according. Secondary data from the Department of Biological Science were used to analyse the findings of this research work. All hypotheses were tested at 0.05 level of significance. The results obtained showed that the four factors interaction is the only significant treatment in the factorial design. Eta squared showed that the four factors (Sex, Age, School, and Mode of Entry) interaction contributes the greatest to the variations in the students’ scores in the subject. Noncent parameter and Observed power showed the same. The study recommended amongst other things that parents and educationists should provide enabling environment for the students by ensuring their age, school, and mode of entry is taken cognizance of as it has a significant impact on the students’ performance; parents who are interested in the educational performance of their children to become Biologists or take up Biology and parents who are tending to mould their children to become Biologists or take up Biology related careers in the future to take these four factors into consideration.